Value of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in the diagnosis of lung and mediastinal lesions - Carbonari,Augusto (2020)
SUMMARY OBJECTIVE: To evaluate the value of EBUS-TBNA in the diagnosis of lung and mediastinal lesions. METHODS: Prospective cohort study that included 52 patients during a 2-year period (2016 to 2018) who underwent EBUS-TBNA. RESULTS: Among the 52 individuals submitted to the procedure, 22 (42.31%) patients were diagnosed with locally advanced lung cancer (N2 or N3 lymph node involvement). EBUS-TBNA confirmed the diagnosis of metastases from other extrathoracic tumors in the mediastinum or lung in 5 patients (9.61%), confirmed small cell lung cancer in 3 patients (5.76%), mediastinal sarcoidosis in 1 patient (1.92%), and reactive mediastinal lymph node in 8 patients (15.38%); insufficient results were found for 3 patients (5.76%). Based on these results, EBUS-TBNA avoided further subsequent surgical procedures in 39 of 52 patients (75%). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 86%, 100%, 100%, 77%, and 90%, respectively. No major complications were observed. CONCLUSIONS: EBUS-TBNA is a safe, effective, and valuable method. This technique can significantly reduce the rate of subsequent surgical procedures required for the diagnosis of lung and mediastinal lesions.